Innovation of ICT-Based English Learning to Improve the Quality of Education During the Covid-19 Pandemic - Pambudi, Teguh Eka; Samoal, Jumiyanti Rahman (Journal of Quality Assurance in Islamic Education (JQAIE), 2022)
ICT is a general term that refers to the technology used to collect, edit, obtain information in various forms One of the biggest challenges in the world of education is how to utilize information and communication technology (ICT) in an academic context Especially during the covid-19 outbreak, all face-to-face education is stopped and diverted to E-learning which requires students to use digital technology to prevent wider spread. ICT-based learning innovation during this pandemic can be done with various applications that can help learning activities such as the Zoom meeting application, which is a virtual classroom application that is used for various activities during the pandemic where the teaching and learning process, discussions, consultations, to cellular collaboration. This research was created to provide information about the existence of technology that can be used as an alternative to new learning innovations in the covid-19 pandemic situation for students. The method used in this research is literature research by critically reviewing or reviewing knowledge, ideas, or findings contained in academic literature.